The Critical Success Factors of Consumer-Based Brand Equity in Yazd Tourism Destination - mohammad hoseyn imani khoshkhou; hamid ayoubi yazdi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2010)
Tourism destination brand equity is defined as the brand assets (or liabilities) linked to a destination`s name and symbol that add to (or subtract from) the services and experiences provided. Each year, the brand equities of different international brands are measured by reputable international institutions. In many cases, the equity value is higher than physical assets and this indicates the importance of the brand issue. Thus recognizing the critical factors that affect brand equity is essential. Due to the cultural and social differences and characteristics of Iran’ tourism destinations, this study, through Konecnik (2007) framework, was conducted to detect the factors that domestic tourists recognize as influencing the brand equity of Yazd. The study population consists of potential tourists which have been available in the entrances of Tehran in the period 15 April to 15 May 2010. For analysis of the data the confirmatory factor analysis was used. This research aims to identify the critical factors which tourists think can affect the brand equity and investigates the importance of each factor in their perspectives. The results of the this study imply that in addition to the brand image, which has been more than 30 years the most important factor for the destination brand evaluation, there are other aspects such as brand loyalty, perceived quality, and brand awareness of tourism destinations, that can directly impact on brand equity of Yazd tourism destination. Among those attributes, brand loyalty has the strongest direct effect on the brand equity, while awareness has the least effect